Critical period of weed competition and yield losses of irrigated common bean (Phaseolus vulgaris L.) in northern Sudan - Idris, Khogali; Elamin, Salah; Omer, Siraj; Mohamed, Elsadig (Gezira Journal of Agricultural Science; Vol 9 No 2 (2011), 2011)
Weeds constitute one of the major biotic constraints that limit production of common bean ( Phaseolus vulgaris L.) in Sudan. A field study was conducted at Hudeiba Research Station Farm, Ed Damer, River Nile State, Sudan, during 1998/99 and 1999/2000 winter seasons, to determine the magnitude of yield losses due to weed competition and identify the critical period of weed competition. Plots were kept weedy for 0, 2, 4, 6 and 8 weeks after sowing, while others were maintained weed-free for the same periods. Unrestricted weed growth reduced grain yield by 33 and 51% in seasons 1998/99 and 1999/2000, respectively. The critical period of weed competition varied between seasons. In the first season, the critical period was found to be between 2 and 6 weeks after sowing, whereas in the second season, it was between 4 and 6 weeks after sowing depending on the level of weed infestation and climatic conditions.    تعتبر الحشائش من المعوقات الرئيسية والمحددة لانتاج محصول الفاصوليا في السودان. أجريت هذه التجربة بمزرعة محطة بحوث الحديبة، الدامر، ولاية نهر النيل، خلال موسمي  الشتاء لعامي 1998/1999 و 1999/2000 م بهدف تحديد حجم الفاقد من الانتاج نتيجة التاثير السلبي للحشائش  علي محصول الفاصوليا والتعرف علي الفترة الحرجة لمنافسة ومكافحة الحشائش. أزيلت الحشائش من الاحواض لفترات صفر، 2، 4، 6 و8 أسابيع من الزراعة، بينما تركت الحشائش دون ازالة لنفس الفترات السابقة. أتضح من الدراسة ان الفقد في انتاج البذور لمحصول الفاصوليا قد بلغ  33% و 51% في الموسمين علي التوالي. أما الفترة الحرجة فكانت مختلفة بين الموسمين حيث كانت بين الاسبوع الثاني و السادس من الزراعة في الموسم الاول و بين الاسبوع الرابع  والسادس  في الموسم الثاني وذلك حسب الظروف المناخية السائدة ومستوي الاصابة بالحشائش.